1985
DOI: 10.1073/pnas.82.24.8448
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal processing of proteins: hemoglobin South Florida, a variant with retention of initiator methionine and N alpha-acetylation.

Abstract: The hemoglobin variant South Florida has been shown by protein sequencing and fast-atom-bombardment mass spectroscopy to have a substitution ofmethionine for the NH2-terminal valine of the (8-globin chain. In addition, there was complete retention of the initiator methionine on the mutant polypeptide. Approximately 20% of the protein was acetylated at the NH2 terminus of the (3 chain. A search of a comprehensive data bank of protein and gene sequences revealed 84 unrelated vertebrate proteins that have not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…However, mass spectrometry data on the intact native nerve globin showed a molecular mass of 18,235 Da, which confirms the absence of the N-terminal methionine and suggests an N-terminal mono-acetylation (ϩ42 Da). This is not so unusual as N-terminal acetylation is one of the most common protein modifications in eukaryotes, occurring on ϳ85% of the different varieties of eukaryotic proteins but rarely on prokaryotic proteins (43,44). We observed two additional molecular mass classes (18,333 and 18,430 Da) that differ from the native mono-acetylated protein by 98 and 196 Da, respectively (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…However, mass spectrometry data on the intact native nerve globin showed a molecular mass of 18,235 Da, which confirms the absence of the N-terminal methionine and suggests an N-terminal mono-acetylation (ϩ42 Da). This is not so unusual as N-terminal acetylation is one of the most common protein modifications in eukaryotes, occurring on ϳ85% of the different varieties of eukaryotic proteins but rarely on prokaryotic proteins (43,44). We observed two additional molecular mass classes (18,333 and 18,430 Da) that differ from the native mono-acetylated protein by 98 and 196 Da, respectively (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…This commonly occurs in protein where the second amino acid is small and neutral. 31 Amino terminal modification is required for the function of alpha-tropomyosin in striated muscle 32 and modifies actin function in Drosophila. 33 The distinct difference in adseverin expression seen between Lin Ϫ Sca ϩ Kit ϩ and Lin Ϫ Sca ϩ Kit Ϫ cells suggests that there is a potential difference in regulation of actin filaments and thereby motility.…”
Section: Resultsmentioning
confidence: 99%
“…From a systematic analysis of the amino-terminal sequences data for various mutant forms of yeast iso-1-cytochrome c, as well as from the data for 82 mature intracellular proteins, Sherman et al (28) concluded that the MAPs from various procaryotes and eucaryotes share similar substrate specificity. Surveys of the protein sequence data bank by Boissel et al (4) and Sherman et al (28) provided similar deduced general sequence features in amino-terminal methionine processing.…”
mentioning
confidence: 99%